2013
DOI: 10.1021/jm400479p
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Functional abeo-Taxane Derivatives Destabilizing Microtubule Equilibrium and Inhibiting NF-κB Activation

Abstract: Taxchinin A, with a 11(15→1)-abeo-taxane skeleton, is a major, but inactive taxoid contained in leaves of Taxus chinensis. In our design of dual-functional antitumor abeo-taxane derivatives, two fragments from antitumor agents with different molecular targets (the N-acyl-3′-phenylisoserine side chain from the antimitotic agent paclitaxel and an α,β-unsaturated carbonyl system from NF-κB inhibitors) were incorporated into the scaffold of taxchinin A. The resulting compounds displayed broad inhibitory effects ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…There are also a number of studies demonstrating a reduction in NF-κB activation together with microtubule destabilisation and cell death. For example, destabilising taxoid derivatives reduced TNFαinduced NF-κB activity in HEK293 cells by up to 6.5-fold (Zhao et al 2013) and Jackman et al (2009) showed that this effect likely involves a requirement for physical interaction between microtubules and the TNF-α receptor activation complex, as well as being able to occur directly, with activation of NF-κB being induced directly by microtubule stabilisers without the presence of TNFα.…”
Section: Discussionmentioning
confidence: 99%
“…There are also a number of studies demonstrating a reduction in NF-κB activation together with microtubule destabilisation and cell death. For example, destabilising taxoid derivatives reduced TNFαinduced NF-κB activity in HEK293 cells by up to 6.5-fold (Zhao et al 2013) and Jackman et al (2009) showed that this effect likely involves a requirement for physical interaction between microtubules and the TNF-α receptor activation complex, as well as being able to occur directly, with activation of NF-κB being induced directly by microtubule stabilisers without the presence of TNFα.…”
Section: Discussionmentioning
confidence: 99%
“…The prominent advantage of employing the molecular hybridization approach is to trigger diverse targets by a sole molecule, thus increasing the therapeutic effectiveness and bioavailability profiles. Promisingly, noteworthy results with a diverse group of heterocyclic hybrids have been elegantly recognized as a result of this approach [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Compounds 1 and 2 were also evaluated for their effects on the NF-κB pathway (Figure 5). 20 Only compound (+)-1 could inhibit TNF-α induced NF-κB activation at 40 μM (Figure 5A). But 2 could activate the NF-κB pathway with the existence of TNF-α, which revealed the synergistic effect of 2 with TNF-α on NF-κB activation (Figure 5B).…”
mentioning
confidence: 98%
“…Compounds 1 and 2 were also evaluated for their effects on the NF-κB pathway (Figure ) . Only compound (+)- 1 could inhibit TNF-α induced NF-κB activation at 40 μM (Figure A).…”
mentioning
confidence: 99%